2009
DOI: 10.1186/1471-2318-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Falls among community-residing stroke survivors following inpatient rehabilitation: a descriptive analysis of longitudinal data

Abstract: BackgroundStroke victims are at relatively high risk for injurious falls. The purpose of this study was to document longitudinal fall patterns following inpatient rehabilitation for first-time stroke survivors.MethodsParticipants (n = 231) were recruited at the end of their rehab stay and interviewed monthly via telephone for 1 to 32 months regarding fall incidents. Analyses were conducted on: total reports of falls by month over time for first-time and repeat fallers, the incidence of falling in any given mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
1
26
1
Order By: Relevance
“…Patients with stroke demonstrate frequent and longitudinal studies with stroke survivors in different clinical conditions are fundamental for a better knowledge of modifi able and/or treatable factors related to fall risk. 24,36,37 Our patients fell mostly while walking, at home, and in the morning, similar to fi ndings in other studies. 33,38,39 These characteristics emphasize the need for preventive programs including patient and caregiver education, routine physical exercise, review of medications affecting balance, routine ophthalmological evaluation, and review of home safety.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with stroke demonstrate frequent and longitudinal studies with stroke survivors in different clinical conditions are fundamental for a better knowledge of modifi able and/or treatable factors related to fall risk. 24,36,37 Our patients fell mostly while walking, at home, and in the morning, similar to fi ndings in other studies. 33,38,39 These characteristics emphasize the need for preventive programs including patient and caregiver education, routine physical exercise, review of medications affecting balance, routine ophthalmological evaluation, and review of home safety.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have used BBS to predict the fall in patients with stroke and found it to be a good predictor of fall [8,16,17]. Also BBS is used to differentiate between fallers and non-fallers [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke still is one of the major chronic diseases around the world [1-4]. It is also considered one of the main causes of disabilities [5] resulting not only in persistent neurological deficits, but also in a high physical deconditioning that propagates disability, leading to metabolic abnormalities that significantly increase the risk of myocardial infarction and recurrent stroke [6].…”
Section: Introductionmentioning
confidence: 99%